Application of non destructive test for structure evaluation - Mohd Zia, Rosli (2010)
The aim of the present paper is to check the accuracy of Ultrasonic Pulse Velocity (UPV) and Rebound Hammer for assessing concrete strength that are widely used in structural field. Even though there are many methods for Non Destructive Test (NDT) but every method have it own boundaries and which mean the method cannot afford an accurate and consistence result for difference cases and to detect different defect. The NDT is applied on jetty Lembaga Kemajuan Ikan Malaysia (LKIM) at Kuantan, Pahang. The structure that has been test is the slab that was constructed in year 1989 and 2001. A general series of tests which are compression test, rebound hammer and UPV was carried out at laboratory to obtain a correlation of the NDT results with compressive strength. 24 concrete cubes of sizes 150 x 150 x 150 nun has been made and subjected to two curing condition which is water curing and air curing for 1 day, 7, 14 and 28 days. For each day stated, 3 cubes which subjected to water curing and 3 cubes subjected to air curing was tested. To get the exact result of the cube strength, compression test applied to the concrete cube. Before the compression testing applied, the cube strength checked by using UPV and rebound hammer. The data obtained from each test has been evaluated and the accurate and precise device was determined. From this research, the most accurate NDT method is Ultrasonic Pulse Velocity.